19th-century French photographs from the National Gallery of Canada / James Borcoman. - Borcoman, James (National Gallery of Canada, 2010)
"The range of photographic vision in the National Gallery's collection of 19th Century French photographs is vast. The collection extends from topographical photographers who made little pretense to art but, because of the sensitivity and skill produced work that transcends the original purpose, to those who considered themselves as artists and the photographs they produced as art. With over 200 illustrations, this abundantly illustrated publication features an original essay on the development of photography in 19th Century France as well as sixty-six individual presentations. Among the dozens of photographers discussed are Eugene Atget, Edouard Baldus, Maxime Du Camp, Gustave Le Gray and Auguste Salzmann." --Book Jacket.